2004
DOI: 10.1097/01.ccm.0000108877.92124.df
|View full text |Cite
|
Sign up to set email alerts
|

Poor correlation between hemodynamic and echocardiographic indexes of left ventricular performance in the operating room and intensive care unit

Abstract: There is a significant discrepancy and limited relationship between the hemodynamic and echocardiographic evaluation of left ventricular performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 24 publications
2
16
0
3
Order By: Relevance
“…This is in accordance with the results of Bouchard and colleagues, who recently demonstrated that there is a significant discrepancy and limited relationship between the haemodynamic and echocardiographic evaluation of left-ventricular performance [25]. As already mentioned by Bendjelid, the results of the Feissel study may be biased, as expiratory flow velocity time integral of aortic blood flow is a shared variable in the calculation of both CI and ⌬Vpeak and a mathematical coupling may contribute to the observed correlation between changes in CI and ⌬Vpeak [22].…”
Section: Bland-altman Plots For Comparison Between the Pcci And The Tsupporting
confidence: 94%
“…This is in accordance with the results of Bouchard and colleagues, who recently demonstrated that there is a significant discrepancy and limited relationship between the haemodynamic and echocardiographic evaluation of left-ventricular performance [25]. As already mentioned by Bendjelid, the results of the Feissel study may be biased, as expiratory flow velocity time integral of aortic blood flow is a shared variable in the calculation of both CI and ⌬Vpeak and a mathematical coupling may contribute to the observed correlation between changes in CI and ⌬Vpeak [22].…”
Section: Bland-altman Plots For Comparison Between the Pcci And The Tsupporting
confidence: 94%
“…Figure 6 performs stroke work changes to mean arterial pressure (for the exercise protocol). As it can be observed, slope of the results reported by this paper (168.08 mmHg·ml/ml) and are within the reported clinical data varied from 46.56 to 335.05 ml [1,2,4,5,12]. The average slope of clinical data is 191.42 mmHg·ml/ml.…”
Section: Clinical Application and Reliabilitysupporting
confidence: 63%
“…For example, the stroke work index is a reliable criterion of left ventricle performance which requires an invasive procedure, and has been usually measured and utilized in the settings of intensive care units and operation rooms [2][3][4]. While invasive methods have been used to measure stroke work, such techniques are expensive and include risks to patients [5].…”
Section: Introductionmentioning
confidence: 99%
“…La primera onda E (early) corresponde al llene temprano del VI y la onda A (auricular) corresponde a la sístole auricular. También se ha visto que la disfunción diastólica se asocia con un mayor número de eventos hemodinámicos postoperatorios, como hipotensión e hipertensión [11][12][13][14][15][16][17] . La Ecocardiografía también permite calcular el gasto cardíaco (GC), parámetro reconocido como un muy buen índi-ce de función cardíaca global y predictor de complicaciones perioperatorias.…”
Section: Ecocardiografía Transesofágica (Ete) Durante Cirugía No Cardunclassified